Tinjauan Maqasid Asy-Syari’ah Terhadap Peraturan Daerah Provinsi Jawa Timur Nomor 16 Tahun 2012 Tentang Penyelenggaraan Perlindungan Perempuan Dan Anak Korban Kekerasan - Muzaiyanah Muzaiyanah (Al-Ahkam: Jurnal Ilmu Syari’ah dan Hukum, 2022)
The author's goal is to discuss the East Java Provincial Regulation Number 16 of 2012's review of maqasid asy-syariah  on sexual violence against women and children in order to provide an understanding of Islam in contemporary Islamic  discourse through maqasid asy-syariah, which includes humanitarian issues,  particularly for women and children. The community is obliged to comply with  regulations such as Regional Regulations (Perda) , despite the fact that there is no express instruction in the Qur’an or Hadith, even during the prophetic era. The need of comprehending maqasid asy-syariah in order to manage human life in order to maximize benefits and minimize harm. The data was analyzed using a descriptive-analytical method based on the maqasid asy-syariah theory. Data collection methods using library material and  previous study. The findings revealed that the Regional Regulation No. 16 of 2012, which  addressed the execution of the protection of women and children victims of  violence, gave attention to the maqasid asy-syariah issues that arose in the  community. This can be determined by referring to the regulation's "weighing" and "remembering" considerations. However, other aspects of the regional rule  are disregarded, such as Article 17's requirement to report sexual abuse against  women and children, for which they will face punishment as outlined in the  applicable laws and regulations.